Preparation method of polymer composition and application of polymer composition in waterproof roll

By using high-density polyethylene and modified filler in the waterproof roll, combined with the design of the modified asphalt glue layer and fine sand layer, the problem of insufficient mechanical properties and peel strength of the traditional waterproof roll material is solved. Achieve higher mechanical properties and better service life.

CN119431933AInactive Publication Date: 2025-02-14GANSU DAYU WATERPROOF TECH DEV CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510039088.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional waterproof coils have shortcomings in terms of mechanical properties and peel strength from post-cast concrete, which is difficult to meet the market's demand for high-performance and environmentally friendly waterproof materials.

Method used

High-density polyethylene and modified fillers are used to prepare polymer compositions and used in waterproof coils. Combined with the design of modified asphalt glue layer and fine sand layer, the mechanical properties and peel strength of the coils are improved.

Benefits of technology

The tension, elongation of break and peel strength from the post-cast concrete of the waterproof coil are significantly improved, and the overall performance and service life of the material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a preparation method of a polymer composition and application of the polymer composition in a waterproof coiled material, and belongs to the technical field of building materials.According to the polymer composition, PA6, modified filler, an antioxidant 1010 and calcium stearate are mixed to form an auxiliary mixture; mixing with high-density polyethylene, ethylene glycidyl methacrylate random copolymer and magnesium hydroxide to form a main mixture, and finally carrying out melt blending extrusion molding; the waterproof coiled material is formed by adopting a double-roller pouring and blade coating process, and structurally comprises a lower surface isolation layer, a double-modified asphalt adhesive layer, a polymer composition layer and an upper surface fine sand layer. Compared with the prior art, the mechanical property, the aging resistance and the peel strength with post-poured concrete of the waterproof coiled material are remarkably improved, the waterproof coiled material has excellent waterproof effect and durability, ultraviolet rays can be effectively blocked, and the service life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a preparation method of a polymer composition and application of the polymer composition in waterproof coiled materials. Background Art

[0002] In the field of building materials technology, especially waterproof materials, waterproof membranes are an important building waterproof material, and their performance is directly related to the waterproof effect and service life of the building. Although traditional waterproof membranes, such as asphalt-based waterproof membranes and polymer waterproof membranes, can meet the waterproofing needs to a certain extent, they still have deficiencies in mechanical properties, aging resistance, and peeling strength with post-cast concrete. With the development of construction technology and the improvement of environmental protection requirements, the market demand for high-performance and environmentally friendly waterproof materials is growing.

[0003] Chinese invention patent CN111635710A discloses a double-base waterproofing membrane and its preparation method. The structure of the double-base waterproofing membrane is, from top to bottom: upper surface isolation layer, upper modified asphalt glue, upper modified polyethylene base, middle modified asphalt glue, lower modified polyethylene base, lower modified asphalt glue, lower surface isolation layer. The double-base waterproofing membrane of the invention has high strength and elongation, which solves the contradiction between the strength and elongation of traditional materials, and has good impermeability and excellent thermal stability, which well guarantees the waterproof effect of the membrane. The invention does not add any recycled materials, which greatly improves the product quality and increases the service life of the product. However, the product prepared by this method still has room for improvement in mechanical properties and peeling strength with post-cast concrete. Summary of the invention

[0004] In order to solve the deficiencies in the prior art, the present invention aims to provide a method for preparing a polymer composition and its application in waterproof membranes, so as to improve the deficiencies of traditional waterproof materials in mechanical properties and peeling strength with post-cast concrete.

[0005] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions: A method for preparing a polymer composition is as follows: 15 parts by weight of PA6 are mixed with 5 parts by weight of modified filler, 0.3 parts by weight of antioxidant 1010 and 0.2 parts by weight of calcium stearate to form a sub-mixture; then, 60 parts by weight of high-density polyethylene, 5 parts by weight of ethylene methacrylate glycidyl ester random copolymer and 0.2 parts by weight of magnesium hydroxide are mixed to form a main mixture; the sub-mixture and the main mixture are mixed; finally, the uniformly mixed materials are melt-blended at 200°C and then extruded and molded to obtain a polymer composition.

[0006] The molding in the present invention is to melt-blend the uniformly mixed polymer composition at 200° C. and then extrude it, and then use a molding device to mold the molten material into a desired shape and size to finally obtain the polymer composition.

[0007] The preparation method of the modified filler is as follows: S1, taking 100 parts by weight of basalt powder, adding it to 2000 parts by weight of 8wt% potassium hydroxide aqueous solution, stirring it at a temperature of 50°C for 2 hours, filtering and drying it after the treatment, and then calcining it at a high temperature of 450°C for 1 hour to obtain a pretreated product; S2, putting 100 parts by weight of the pre-treated product into 2000 parts by weight of a 70wt% ethanol aqueous solution, adding 10 parts by weight of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, and keeping at a temperature of 70°C for 3 hours, then filtering, washing and drying to obtain a post-treated product; S3. Add 100 parts by weight of the post-treated product to 2000 parts by weight of dimethyl sulfoxide, then add 12 parts by weight of N,N'-bis(acryl)cystamine and 0.6 parts by weight of ammonium persulfate as initiators, react at a temperature of 90°C for 4 hours, and then obtain a modified filler by filtering, washing and drying.

[0008] Application of the polymer composition in waterproof roll materials.

[0009] The preparation method of the waterproof coiled material is as follows: The lower surface isolation layer, the second modified asphalt adhesive layer and the polymer composite layer are formed by the double-roll casting process, the first modified asphalt adhesive layer is formed by the double-roll casting process, and finally the upper surface fine sand layer is formed by the scraping process. After cooling, the waterproof membrane is obtained. The polymer composite layer is the polymer composition. The waterproof membrane is composed of the lower surface isolation layer, the second modified asphalt adhesive layer, the polymer composite layer, the first modified asphalt adhesive layer and the upper surface fine sand layer from bottom to top.

[0010] The lower surface isolation layer is a PE layer with a thickness of 0.02 mm.

[0011] The upper surface fine sand layer is composed of 40 mesh fine sand and has a thickness of 1.5 mm.

[0012] The thickness of the polymer composite layer is 0.5 mm.

[0013] The first modified asphalt adhesive layer and the second modified asphalt adhesive layer are both made of the same modified asphalt adhesive. The thickness of the first modified asphalt adhesive layer is 1 mm, and the thickness of the second modified asphalt adhesive layer is 1 mm.

[0014] The preparation method of the modified asphalt rubber is as follows: 50 parts by weight of petroleum asphalt and 10 parts by weight of cyclohexane oil KN4010 are mixed and heated to 125°C to form a mixture A; then the mixture A is heated to 160°C, 2 parts by weight of butyl rubber is added and stirred for 30 minutes to obtain a mixture B; then the mixture B is heated to 200°C, 6 parts by weight of SBS rubber and 2 parts by weight of SIS rubber are added while maintaining the temperature, and the mixture is mixed for 2 hours to obtain a mixture C; then 4 parts by weight of polypropylene particles are added to the mixture C, and the mixture is mixed and ground for 2 hours to form a mixture D; finally, 20 parts by weight of talcum powder is added to the mixture D, and the mixture is mixed at 175°C for 2 hours to obtain the modified asphalt rubber.

[0015] The functions of the various substances described in the present invention are as follows: As one of the main components of the polymer composition, PA6 provides the mechanical properties and thermal stability of the material.

[0016] The modified filler enhances the mechanical properties of the polymer composition, increases the peel strength with the post-cast concrete, and improves the overall performance of the material.

[0017] Antioxidant 1010 improves the aging resistance of the material and extends the service life of the material.

[0018] Calcium stearate acts as a stabilizer and lubricant to improve the processing properties of the material.

[0019] High-density polyethylene, as another major component of the polymer composition, provides water resistance and enhances the material's resistance to environmental stress cracking.

[0020] Ethylene methacrylate glycidyl ester random copolymer improves the bonding performance and water resistance of the material.

[0021] Magnesium hydroxide acts as a flame retardant and heat stabilizer to improve the flame retardancy and thermal stability of the material.

[0022] 2,4,6-Trivinyl-2,4,6-trimethylcyclotrisiloxane is used as a silane coupling agent to enhance the interfacial bonding force between the modified filler and the polymer PA6 and improve the mechanical properties of the material.

[0023] N,N'-bis(acryl)cystamine is used as a cross-linking agent to provide dynamic cross-linking points for the material, thereby enhancing the toughness and elasticity of the material and improving the self-healing ability of the material.

[0024] Ammonium persulfate is used as an initiator to promote the cross-linking reaction of N,N'-bis(acryl)cystamine.

[0025] Petroleum asphalt is used as the base material of modified asphalt adhesive, providing waterproofing and bonding properties.

[0026] Naphthenic oil KN4010 improves the fluidity and viscosity of petroleum asphalt, making it easier to process.

[0027] Butyl rubber improves the elasticity and aging resistance of modified asphalt rubber.

[0028] SBS rubber improves the elasticity and low temperature resistance of modified asphalt rubber.

[0029] SIS rubber improves the bonding performance and aging resistance of modified asphalt adhesive.

[0030] Polypropylene particles improve the mechanical properties and chemical corrosion resistance of modified asphalt glue.

[0031] Talc is used as a filler in modified asphalt rubber to improve the material's heat resistance and chemical corrosion resistance.

[0032] The combination and interaction of these substances enable the polymer composition of the present invention and the preparation method thereof to significantly improve the performance of the waterproof membrane, including mechanical properties, aging resistance, peeling strength with post-cast concrete, etc.

[0033] Compared with the prior art, it has the following beneficial effects: 1) The present invention significantly improves the tensile force and elongation at break of the waterproofing membrane by using a specific polymer composition and modified filler, thereby enhancing the mechanical properties of the material. This makes the membrane perform better in terms of damage resistance and elongation performance, and can better adapt to different construction environments and application requirements.

[0034] 2) The waterproof membrane of the present invention performs better in terms of peeling strength with post-cast concrete, thanks to the use of modified fillers and specific chemical additives, which enhance the adhesion between the membranes. This enhanced peeling strength helps to improve the waterproofing effect and durability of the membrane in practical applications.

[0035] 3) The present invention effectively blocks the direct contact between ultraviolet rays and the adhesive layer by covering the surface of the coil with a fine sand layer, thereby playing an anti-aging role. This design not only protects the coil from damage by ultraviolet rays, but also extends the service life of the product and improves its stability and reliability in long-term applications. DETAILED DESCRIPTION

[0036] Main sources of substances: Petroleum asphalt, grade 90, flash point: 240℃, Hebei Deri New Material Technology Co., Ltd.

[0037] Talc, 325 mesh.

[0038] Naphthenic oil KN4010, Hengshui Kaientai Oil Co., Ltd.

[0039] Butyl rubber, brand: 1675, Shanghai Jiuqing Chemical Co., Ltd.

[0040] SBS rubber, brand: 791, manufacturer: Baling Petrochemical.

[0041] SIS rubber, item number: YH-1105-5, manufacturer: Baling Petrochemical.

[0042] Polypropylene granules, brand: K7726, manufacturer: Yanshan Petrochemical.

[0043] PA6, brand: YH800, manufacturer: Baling Petrochemical.

[0044] High-density polyethylene, brand: 1508S, manufacturer: Yanshan Petrochemical.

[0045] Ethylene methacrylate glycidyl ester random copolymer, brand: AX8900, characteristic level: transparent grade, type: EMA, brand: French Arkema Basalt powder, item number: h858558, particle size: 325 mesh, Lingshou Yixin Mineral Products Processing Plant.

[0046] Kaolin, particle size: 325 mesh.

[0047] Vermiculite powder, 200 mesh, silicon dioxide content: 45%, magnesium oxide content: 15%.

[0048] Diatomaceous earth, particle size: 325 mesh, SiO2 content ≥95%.

[0049] The remaining raw materials in the examples and comparative examples of the present invention are all commercially available products.

[0050] The design idea of ​​the present invention is to provide a polymer composition and a preparation method thereof, and apply it to the manufacture of waterproof roll materials to improve the deficiencies of traditional waterproof materials in terms of mechanical properties and peeling strength with post-cast concrete. By selecting high-density polyethylene as the matrix material and using surface-coated fine sand technology on the base plate, the present invention aims to enhance the waterproof roll material's anti-breakage ability, elongation performance and waterproof performance, while utilizing the combination of modified asphalt adhesive layer and fine sand layer to improve the adhesion between the roll material and post-cast concrete, and utilizing the fine sand layer to block ultraviolet rays and play an anti-aging role, thereby improving the overall performance and service life of the waterproof roll material.

[0051] Example 1

[0052] A method for preparing a waterproof coiled material is as follows: The lower surface isolation layer, the second modified asphalt adhesive layer and the polymer composite layer formed by the roller casting process, the first modified asphalt adhesive layer formed by the roller casting process, and the upper surface fine sand layer formed by the scraping process are cooled to obtain a waterproof membrane. The polymer composite layer is the polymer composition. The waterproof membrane is composed of the lower surface isolation layer, the second modified asphalt adhesive layer, the polymer composite layer, the first modified asphalt adhesive layer, and the upper surface fine sand layer from bottom to top; the lower surface isolation layer is a PE layer with a thickness of 0.02mm, the upper surface fine sand layer is composed of 40 mesh fine sand with a thickness of 1.5mm, and the thickness of the polymer composition is 0.5mm, wherein the first modified asphalt adhesive layer and the second modified asphalt adhesive layer are prepared by the same modified asphalt adhesive. The thickness of the first modified asphalt rubber layer is 1 mm, and the thickness of the second modified asphalt rubber layer is 1 mm. The preparation method of the modified asphalt rubber is as follows: 50 parts by weight of petroleum asphalt and 10 parts by weight of cyclohexane oil KN4010 are mixed and heated to 125°C to form a mixture A; then the mixture A is heated to 160°C, 2 parts by weight of butyl rubber are added and stirred for 30 minutes to obtain a mixture B; then the mixture B is heated to 200°C, 6 parts by weight of SBS rubber and 2 parts by weight of SIS rubber are added while maintaining the temperature, and the mixture is mixed for 2 hours to obtain a mixture C; then 4 parts by weight of polypropylene particles are added to the mixture C, and the mixture is mixed and ground for 2 hours to form a mixture D; finally, 20 parts by weight of talcum powder are added to the mixture D, and the mixture is mixed at 175°C for 2 hours to obtain the modified asphalt rubber.

[0053] The preparation method of the polymer composition is as follows: 15 parts by weight of PA6 are mixed with 5 parts by weight of modified filler, 0.3 parts by weight of antioxidant 1010 and 0.2 parts by weight of calcium stearate to form a sub-mixture; then, 60 parts by weight of high-density polyethylene, 5 parts by weight of ethylene methacrylate glycidyl ester random copolymer and 0.2 parts by weight of magnesium hydroxide are mixed to form a main mixture; the sub-mixture and the main mixture are mixed; finally, the uniformly mixed materials are melt-blended at 200°C and then extruded and molded to obtain a polymer composition.

[0054] The preparation method of the modified filler is as follows: S1, taking 100 parts by weight of basalt powder, adding it to 2000 parts by weight of 8wt% potassium hydroxide aqueous solution, stirring it at a temperature of 50°C for 2 hours, filtering and drying it after the treatment, and then calcining it at a high temperature of 450°C for 1 hour to obtain a pretreated product; S2, putting 100 parts by weight of the pre-treated product into 2000 parts by weight of a 70wt% ethanol aqueous solution, adding 10 parts by weight of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, and keeping at a temperature of 70°C for 3 hours, then filtering, washing and drying to obtain a post-treated product; S3. Add 100 parts by weight of the post-treated product to 2000 parts by weight of dimethyl sulfoxide, then add 12 parts by weight of N,N'-bis(acryl)cystamine and 0.6 parts by weight of ammonium persulfate as initiators, react at a temperature of 90°C for 4 hours, and then obtain a modified filler by filtering, washing and drying.

[0055] Example 2

[0056] The preparation method of a waterproof coiled material is basically the same as that of Example 1, the only difference being that the preparation method of the modified filler is different.

[0057] The preparation method of the modified filler is as follows: S1, taking 100 parts by weight of kaolin, adding it to 2000 parts by weight of 8wt% potassium hydroxide aqueous solution, stirring it at a temperature of 50°C for 2 hours, filtering and drying it after the treatment, and then calcining it at a high temperature of 450°C for 1 hour to obtain a pretreated product; S2, putting 100 parts by weight of the pre-treated product into 2000 parts by weight of a 70wt% ethanol aqueous solution, adding 10 parts by weight of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, and keeping at a temperature of 70°C for 3 hours, then filtering, washing and drying to obtain a post-treated product; S3. Add 100 parts by weight of the post-treated product to 2000 parts by weight of dimethyl sulfoxide, then add 12 parts by weight of N,N'-bis(acryl)cystamine and 0.6 parts by weight of ammonium persulfate as initiators, react at a temperature of 90°C for 4 hours, and then obtain a modified filler by filtering, washing and drying.

[0058] Example 3

[0059] The preparation method of a waterproof coiled material is basically the same as that of Example 1, the only difference being that the preparation method of the modified filler is different.

[0060] The preparation method of the modified filler is as follows: S1, take 100 parts by weight of vermiculite powder, add it to 2000 parts by weight of 8wt% potassium hydroxide aqueous solution, stir it for 2 hours at a temperature of 50°C, filter and dry it after the treatment, and then calcine it at a high temperature of 450°C for 1 hour to obtain a pretreated product; S2, putting 100 parts by weight of the pre-treated product into 2000 parts by weight of a 70wt% ethanol aqueous solution, adding 10 parts by weight of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, and keeping at a temperature of 70°C for 3 hours, then filtering, washing and drying to obtain a post-treated product; S3. Add 100 parts by weight of the post-treated product to 2000 parts by weight of dimethyl sulfoxide, then add 12 parts by weight of N,N'-bis(acryl)cystamine and 0.6 parts by weight of ammonium persulfate as initiators, react at a temperature of 90°C for 4 hours, and then obtain a modified filler by filtering, washing and drying.

[0061] Example 4

[0062] The preparation method of a waterproof coiled material is basically the same as that of Example 1, the only difference being that the preparation method of the modified filler is different.

[0063] The preparation method of the modified filler is as follows: S1, taking 100 parts by weight of basalt powder, adding it to 2000 parts by weight of 8wt% potassium hydroxide aqueous solution, stirring it at a temperature of 50°C for 2 hours, filtering and drying it after the treatment, and then calcining it at a high temperature of 450°C for 1 hour to obtain a pretreated product; S2, putting 100 parts by weight of the pre-treated product into 2000 parts by weight of a 70 wt % ethanol aqueous solution, adding 10 parts by weight of tri(isopropenyloxy)vinylsilane, and keeping at a temperature of 70° C. for 3 hours, then filtering, washing and drying to obtain a post-treated product; S3. Add 100 parts by weight of the post-treated product to 2000 parts by weight of dimethyl sulfoxide, then add 12 parts by weight of N,N'-bis(acryl)cystamine and 0.6 parts by weight of ammonium persulfate as initiators, react at a temperature of 90°C for 4 hours, and then obtain a modified filler by filtering, washing and drying.

[0064] Example 5

[0065] The preparation method of a waterproof coiled material is basically the same as that of Example 1, the only difference being that the preparation method of the modified filler is different.

[0066] The preparation method of the modified filler is as follows: S1, taking 100 parts by weight of basalt powder, adding it to 2000 parts by weight of 8wt% potassium hydroxide aqueous solution, stirring it at a temperature of 50°C for 2 hours, filtering and drying it after the treatment, and then calcining it at a high temperature of 450°C for 1 hour to obtain a pretreated product; S2, putting 100 parts by weight of the pre-treated product into 2000 parts by weight of a 70 wt% ethanol aqueous solution, adding 10 parts by weight of diethoxydivinylsilane, and keeping at a temperature of 70° C. for 3 hours, then filtering, washing and drying to obtain a post-treated product; S3. Add 100 parts by weight of the post-treated product to 2000 parts by weight of dimethyl sulfoxide, then add 12 parts by weight of N,N'-bis(acryl)cystamine and 0.6 parts by weight of ammonium persulfate as initiators, react at a temperature of 90°C for 4 hours, and then obtain a modified filler by filtering, washing and drying.

[0067] Example 6

[0068] The preparation method of a waterproof coiled material is basically the same as that of Example 1, the only difference being that the preparation method of the modified filler is different.

[0069] The preparation method of the modified filler is as follows: S1, taking 100 parts by weight of basalt powder, adding it to 2000 parts by weight of 8wt% potassium hydroxide aqueous solution, stirring it at a temperature of 50°C for 2 hours, filtering and drying it after the treatment, and then calcining it at a high temperature of 450°C for 1 hour to obtain a pretreated product; S2, putting 100 parts by weight of the pre-treated product into 2000 parts by weight of a 70wt% ethanol aqueous solution, adding 10 parts by weight of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, and keeping at a temperature of 70°C for 3 hours, then filtering, washing and drying to obtain a post-treated product; S3. Add 100 parts by weight of the post-treated product to 2000 parts by weight of dimethyl sulfoxide, then add 12 parts by weight of N,N'-vinylbisacrylamide and 0.6 parts by weight of ammonium persulfate as initiators, react at a temperature of 90°C for 4 hours, and then obtain a modified filler by filtering, washing and drying.

[0070] Comparative Example 1 The preparation method of a waterproof coiled material is basically the same as that of Example 1, the only difference being that the preparation method of the modified filler is different.

[0071] The preparation method of the modified filler is as follows: S1, taking 100 parts by weight of diatomaceous earth, adding it to 2000 parts by weight of 8wt% potassium hydroxide aqueous solution, stirring it at a temperature of 50°C for 2 hours, filtering and drying it after the treatment, and then calcining it at a high temperature of 450°C for 1 hour to obtain a pretreated product; S2, putting 100 parts by weight of the pre-treated product into 2000 parts by weight of a 70wt% ethanol aqueous solution, adding 10 parts by weight of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, and keeping at a temperature of 70°C for 3 hours, then filtering, washing and drying to obtain a post-treated product; S3. Add 100 parts by weight of the post-treated product to 2000 parts by weight of dimethyl sulfoxide, then add 12 parts by weight of N,N'-bis(acryl)cystamine and 0.6 parts by weight of ammonium persulfate as initiators, react at a temperature of 90°C for 4 hours, and then obtain a modified filler by filtering, washing and drying.

[0072] Comparative Example 2 The preparation method of a waterproof coiled material is basically the same as that of Example 1, the only difference being that the preparation method of the modified filler is different.

[0073] The preparation method of the modified filler is as follows: S1, taking 100 parts by weight of basalt powder, adding it to 2000 parts by weight of 8wt% potassium hydroxide aqueous solution, stirring it at a temperature of 50°C for 2 hours, filtering and drying it after the treatment, and then calcining it at a high temperature of 450°C for 1 hour to obtain a pretreated product; S2, putting 100 parts by weight of the pre-treated product into 2000 parts by weight of a 70wt% ethanol aqueous solution, adding 10 parts by weight of vinyltriethoxysilane, and keeping at a temperature of 70°C for 3 hours, then filtering, washing and drying to obtain a post-treated product; S3. Add 100 parts by weight of the post-treated product to 2000 parts by weight of dimethyl sulfoxide, then add 12 parts by weight of N,N'-bis(acryl)cystamine and 0.6 parts by weight of ammonium persulfate as initiators, react at a temperature of 90°C for 4 hours, and then obtain a modified filler by filtering, washing and drying.

[0074] Comparative Example 3 The preparation method of a waterproof coiled material is basically the same as that of Example 1, the only difference being that the preparation method of the modified filler is different.

[0075] The preparation method of the modified filler is as follows: S1, taking 100 parts by weight of basalt powder, adding it to 2000 parts by weight of 8wt% potassium hydroxide aqueous solution, stirring it at a temperature of 50°C for 2 hours, filtering and drying it after the treatment, and then calcining it at a high temperature of 450°C for 1 hour to obtain a pretreated product; S2, putting 100 parts by weight of the pre-treated product into 2000 parts by weight of a 70wt% ethanol aqueous solution, adding 10 parts by weight of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, and keeping at a temperature of 70°C for 3 hours, then filtering, washing and drying to obtain a post-treated product; S3. Add 100 parts by weight of the post-treated product to 2000 parts by weight of dimethyl sulfoxide, then add 12 parts by weight of 2-acrylamide-2-methylpropanesulfonic acid N-(hydroxymethyl)acrylamide and 0.6 parts by weight of ammonium persulfate as initiators, react at a temperature of 90°C for 4 hours, and then obtain a modified filler by filtering, washing and drying.

[0076] Comparative Example 4 A method for preparing a waterproof roll material is substantially the same as that of Example 1, the only difference being that the modified filler is replaced with an equal amount of basalt powder.

[0077] Test Example 1 Mechanical properties test The tensile force and elongation at break of the waterproof membranes prepared in the examples and comparative examples were tested with reference to the test method in GB / T 18967-2009 "Modified asphalt polyethylene waterproof membrane". Specific test data are shown in Table 1;

[0078] Test Example 2 Peel strength test with post-cast concrete The waterproof membranes prepared in the examples and comparative examples were tested according to the GB / T 23457-2017 standard "Pre-laid waterproof membranes". The test results are shown in Table 2;

[0079] It can be seen from the data of test examples 1 and 2 that the waterproof membrane prepared in Example 1 has the best mechanical properties and peeling strength with post-cast concrete.

[0080] The basalt powder used in Example 1 can more effectively enhance the mechanical properties of the material and the peeling strength with the post-cast concrete when used as a modified filler in the waterproof roll due to its unique physical and chemical properties, such as high thermal stability, high strength, and high modulus. These characteristics of basalt powder help to form a more uniform stress distribution in the polymer composition, improving the overall strength and durability of the material. In contrast, although kaolin, vermiculite powder and diatomaceous earth also have a certain reinforcing effect, these characteristics of basalt powder make it more effective in improving the performance of waterproof rolls, thereby performing best in mechanical properties and peeling strength tests. In addition, the high melting point and heat resistance of basalt powder may help to improve the temperature resistance of waterproof rolls, which is particularly important for the application of rolls in high temperature environments. Therefore, these comprehensive characteristics of basalt powder make it show better performance than other fillers in the preparation of the waterproof roll of the present invention.

[0081] The 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane used in Example 1 has a unique molecular structure compared to the silane coupling agents used in other embodiments and comparative examples, which contains three vinyl groups and three silicon atoms, which enables it to provide more reaction sites in the preparation process of the modified filler. This structure can form more chemical bonds with the surface of basalt powder and PA6 in the polymer composition, thereby enhancing the interfacial bonding force. Since the three vinyl groups can participate in the polymer network, the compatibility and interaction between the modified filler and PA6 are improved, which not only enhances the overall mechanical properties of the waterproof membrane, but also improves the peeling strength with the post-cast concrete. In contrast, other silane coupling agents provide an interface enhancement effect that is not as good as 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane due to the small or different number of reactive functional groups in the molecular structure, so they are not as good as Example 1 in terms of mechanical properties and peeling strength.

[0082] N, N'-bis (acryl) cystamine contains disulfide bonds, and this structure provides dynamic cross-linking points in the material. Disulfide bonds are prone to breakage and reformation under stress, and this dynamic bond exchange helps the material to self-repair when damaged. This characteristic of disulfide bonds makes the material containing N, N'-bis (acryl) cystamine have better toughness and elasticity, so it performs better in mechanical properties and peel strength. In contrast, although N, N'-vinyl bis acrylamide and 2-acrylamido-2-methylpropanesulfonic acid N- (hydroxymethyl) acrylamide also contain active groups, they do not have the dynamic bond exchange characteristics of disulfide bonds. Therefore, the cross-linked network they form in the material may be more rigid, not as good as the material containing N, N'-bis (acryl) cystamine, which can self-repair after damage, and thus is not as good as the material using N, N'-bis (acryl) cystamine in Example 1 in terms of mechanical properties and peel strength.

Claims

1. A method for preparing a polymer composition, characterized in that: Here’s how: 15 parts by weight of PA6 are mixed with 5 parts by weight of modified filler, 0.3 parts by weight of antioxidant 1010 and 0.2 parts by weight of calcium stearate to form a secondary mixture; then, 60 parts by weight of high-density polyethylene, 5 parts by weight of ethylene methacrylate glycidyl ester random copolymer and 0.2 parts by weight of magnesium hydroxide are mixed to form a primary mixture; the secondary mixture and the primary mixture are mixed; finally, the uniformly mixed materials are melt-blended at 200° C. and then extruded and molded to obtain a polymer composition; The preparation method of the modified filler is as follows: S1, taking 100 parts by weight of basalt powder, adding it to 2000 parts by weight of 8wt% potassium hydroxide aqueous solution, stirring it at a temperature of 50°C for 2 hours, filtering and drying it after the treatment, and then calcining it at a high temperature of 450°C for 1 hour to obtain a pretreated product; S2, putting 100 parts by weight of the pre-treated product into 2000 parts by weight of a 70wt% ethanol aqueous solution, adding 10 parts by weight of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, and keeping at a temperature of 70°C for 3 hours, then filtering, washing and drying to obtain a post-treated product; S3. Add 100 parts by weight of the post-treated product to 2000 parts by weight of dimethyl sulfoxide, then add 12 parts by weight of N,N'-bis(acryl)cystamine and 0.6 parts by weight of ammonium persulfate as initiators, react at a temperature of 90°C for 4 hours, and then obtain a modified filler by filtering, washing and drying.

2. A polymer composition, characterized in that The preparation method is as claimed in claim 1.

3. Use of the polymer composition as claimed in claim 2 in waterproof membrane.

4. Use of the polymer composition according to claim 3 in waterproof roll material, characterized in that: The steps include: The lower surface isolation layer, the second modified asphalt adhesive layer and the polymer composite layer are formed by the double-roll casting process, the first modified asphalt adhesive layer is formed by the double-roll casting process, and finally the upper surface fine sand layer is formed by the scraping process. After cooling, the waterproof membrane is obtained. The polymer composite layer is the polymer composition. The waterproof membrane is composed of the lower surface isolation layer, the second modified asphalt adhesive layer, the polymer composite layer, the first modified asphalt adhesive layer and the upper surface fine sand layer from bottom to top.

5. Use of the polymer composition according to claim 4 in waterproof roll material, characterized in that: The lower surface isolation layer is a PE layer with a thickness of 0.02 mm.

6. Use of the polymer composition according to claim 4 in waterproof roll material, characterized in that: The upper surface fine sand layer is composed of 40 mesh fine sand and has a thickness of 1.5 mm.

7. Use of the polymer composition according to claim 4 in a waterproof roll material, characterized in that: The thickness of the polymer composite layer is 0.5 mm.

8. Use of the polymer composition according to claim 4 in waterproofing coiled materials, characterized in that: The first modified asphalt adhesive layer and the second modified asphalt adhesive layer are both made of the same modified asphalt adhesive. The thickness of the first modified asphalt adhesive layer is 1 mm, and the thickness of the second modified asphalt adhesive layer is 1 mm.

9. Use of the polymer composition according to claim 8 in waterproofing coiled materials, characterized in that: The preparation method of the modified asphalt rubber is as follows: 50 parts by weight of petroleum asphalt and 10 parts by weight of cyclohexane oil KN4010 are mixed and heated to 125°C to form a mixture A; then the mixture A is heated to 160°C, 2 parts by weight of butyl rubber is added and stirred for 30 minutes to obtain a mixture B; then the mixture B is heated to 200°C, 6 parts by weight of SBS rubber and 2 parts by weight of SIS rubber are added while maintaining the temperature, and the mixture is mixed for 2 hours to obtain a mixture C; then 4 parts by weight of polypropylene particles are added to the mixture C, and the mixture is mixed and ground for 2 hours to form a mixture D; finally, 20 parts by weight of talcum powder is added to the mixture D, and the mixture is mixed at 175°C for 2 hours to obtain the modified asphalt rubber.

Citation Information

Patent Citations

  • Flame-retardant type modified bituminous waterproof sheet material and production method thereof

    CN108049507A

  • Basalt fiber composite material for manufacturing vehicle body, and preparation method thereof

    CN108546353A

  • Double-base waterproof roll and preparation method thereof

    CN111635710A

  • Embedded pre-paved waterproof coiled material with physical mortise and tenon structure and preparation method of embedded pre-paved waterproof coiled material

    CN115635745A

  • Modified asphalt waterproof coiled material as well as preparation method and application thereof

    CN115785843A